Enfermagem na equipa de saúde ocupacional - Santos, Mónica (2013)
Portuguese law does not define the precise qualifications of occupational health nurses or their role in the occupational health team. A literature review was carried out using the keywords “nursing work and occupational health,” in the databases Medline with Full Text, MedicLatina, Academic Search, CINAHL Plus with Full Text, Cochrane Central Register of Controlled Trials, Cochrane Database of Systemic Reviews, Cochrane Methodology Register, Nursing and Allied Health Collection, Health Technology Assess and NHS Economic Evaluation Database, The aim was to understand the place of nursing in occupational health, describing how this is implemented in different countries with different perspectives and goals. Occupational health now uses a comprehensive approach which includes non-work aspects that interfere with worker health and may include family and/or community. Internationally, predominantly curative tasks have given way to others centered on prevention and management, with numerous programs that the occupational health nurse is able to lead, assuming a central role, fully integrated within the team. Finally, it is crucial to quantify costs, before and after activities, to evaluate the work financially for the management of the employer.